2020
DOI: 10.1007/s13312-020-1756-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Critical Pertussis in Children at a Pediatric Intensive Care Unit in Northern India

Abstract: Objective: To delineate the clinical profile, complications, intensive care needs, and predictors of mortality in children with critical pertussis. Methods: Retrospective analysis of case records of children in the pediatric intensive care unit of a tertiary-care hospital, with a diagnosis of critical pertussis over 3 years. Diagnostic criteria included CDC case definition and confirmation by polymerase chain reaction (PCR), when available. Survivors and nonsurvivors were compared to identify predictors of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Indeed, infant mortality rates due to pertussis ranges between 5.6% and 14.7% in the region [37]. In India, review of 36 pertussis cases admitted to the pediatric intensive care unit showed that 27.7% of those infected were infants below six weeks of age, the youngest age to receive the first dose of the tetanus-diphtheria-pertussis vaccine [36,38].…”
Section: Maternal Tdap Vaccinationmentioning
confidence: 99%
“…Indeed, infant mortality rates due to pertussis ranges between 5.6% and 14.7% in the region [37]. In India, review of 36 pertussis cases admitted to the pediatric intensive care unit showed that 27.7% of those infected were infants below six weeks of age, the youngest age to receive the first dose of the tetanus-diphtheria-pertussis vaccine [36,38].…”
Section: Maternal Tdap Vaccinationmentioning
confidence: 99%
“…This is a case record review, with cases having been evaluated between December, 2018 and June, 2019 at a tertiary care pediatric center in Southern India. All children (up to 18 years) with first afebrile (apparently unprovoked) seizure presenting to emergency room were evaluated and treated as per standard protocol [1]. The necessary investigations like blood sugar, serum electrolytes, electroencephalography (EEG) and neuroimaging were done, with extent of evaluation varying on case-to-case basis, and treating physician's discretion.…”
Section: R R R R R E E E E E S S S S S E E E E E a A A A A R R R R R C C C C C H H H H H L L L L L E E E E E T T T T T T T T T T E E E E mentioning
confidence: 99%
“…The pertussis vaccine is effective in preventing Bordetella pertussis infection and death, and the risk is high in young infants who do not receive the vaccine [1]. B. pertussis infection in siblings is considered a common route of transmission to young infants [2].…”
Section: Pertussis Epidemic In Lower-grade Schoolchildren Without Preschool Vaccination Boostersmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakistan has achieved the Millennium Development Goal of reducing infant mortality [4][5] . The Sustainable Development Goals aim to reduce infant mortality to at least 12 per 1,000 live births by 2030 6 . The downward trend in mortality has been even more impressive so far, especially for infants with very low birth weight <500 g birth weight.…”
Section: Introductionmentioning
confidence: 99%